Entrepreneurship and the social integration of new minorities: Iranian hospitality entrepreneurs in Scotland - Pechlaner, Harald; Lee, T.; Crotts, J.; Mostajer Haghighi, A.; Lynch, P. (Emerald Group Publishing Limited, 2012)
The purpose of this paper is to look at perspectives of new minority entrepreneurs towards entrepreneurship, either as a facilitator or as a barrier to the integration of minorities. The research objective is to explore the role of hospitality and tourism entrepreneurship in the integration process of new minorities. It is attempted to explore the perspectives of new minority entrepreneurs about the concept of integration, the possibility of integration through self-employment in hospitality and the relationship between entrepreneurship and integration. This research adopts a subjective perspective and a social constructionist approach to understand what the new minorities perceive as their reality. An in-depth qualitative methodology is adopted for this research as it tries to understand inductively the phenomenon of hospitality entrepreneurship and ethnic minority integration. The findings suggest hospitality entrepreneurship can act both as a facilitator and as a barrier to integration of the new minorities. Although it facilitates economic integration of the new minorities into the host society by providing wealth for them, at the same time it acts as a barrier to their social and cultural integration. It was revealed that ultimate integration is not possible because of high cultural differences between the host and their original cultures. The paper proposes that integration is a continuum rather than a predefined point to achieve. Integration happens between two extreme points of complete isolation of migrants to their complete assimilation. The respondents of this research did not locate themselves in either ends of this continuum. © 2012, MCB UP Limited